The sensitivity of the trivariate analysis using maternal serum alpha-feto protein, human chorionic gonadotrophin and maternal age in screening for fetal aneuploidy in mothers above the age of 35 - Anandakumar, C. (2016)
10.1515/JPM.1999.024